Aerobic Vitamin B12 Biosynthesis Is Essential for Pseudomonas aeruginosa Class II Ribonucleotide Reductase Activity During Planktonic and Biofilm Growth - Crespo, Anna; Blanco-Cabra, Núria; Torrents, Eduard (Frontiers in Microbiology, 2018)
P. aeruginosa is a major pathogenic bacterium in chronic infections and is a model organism for studying biofilms. P. aeruginosa is considered an aerobic bacterium, but in the presence of nitrate, it also grows in anaerobic conditions. Oxygen diffusion through the biofilm generates metabolic and genetic diversity in P. aeruginosa growth, such as in ribonucleotide reductase activity. These essential enzymes are necessary for DNA synthesis and repair. Oxygen availability determines the activity of the three-ribonucleotide reductase (RNR) classes. Class II and III RNRs are active in the absence of oxygen; however, class II RNRs, which are important in P. aeruginosa biofilm growth, require a vitamin B12 cofactor for their enzymatic activity. In this work, we elucidated the conditions in which class II RNRs are active due to vitamin B12 concentration constraints (biosynthesis or environmental availability). We demonstrated that increased vitamin B12 levels during aerobic, stationary and biofilm growth activate class II RNR activity. We also established that the cobN gene is essentially responsible for B12 biosynthesis under planktonic and biofilm growth. Our results unravel the mechanisms of dNTP synthesis by P. aeruginosa during biofilm growth, which appear to depend on the bacterial strain (laboratory-type or clinical isolate).